Adding Social Media to e-Learning in the Workplace: Instilling Interactive Learning Culture - Leino, Juha; Tanhua-Piiroinen, Erika; Sommers-Piiroinen, Johanna (International Journal of Advanced Corporate Learning (iJAC), 2012)
As social media features are increasingly added to e-learning, we urgently need more case studies of their use to ground practices in actual experience rather than hype. Using ethnography-based approach, we studied five continuous pro-fessional development pilot trainings where learning largely took place at workplace through wikis, blogs, forums, chats and voice conferencing. Learners valued interactivity, peer support and abundant, instant feedback offered by synchro-nous features. Simultaneously, however, asynchronous fea-tures were often treated as chores and overall interactive learning culture failed to emerge. Instructors, while explicitly encouraging social learning approach, implicitly reinforced teacher-centered learning, leading learners to stick to conven-tional learning culture. Also, training designs often failed to engender interaction. Moreover, at general level, group sizes were too big, moderation was not used efficiently, and differ-ing skill sets of learners were not evened out. The lessons learned from these trainings offer us insight into how to design e-learning enhanced with social media and how to avoid po-tential pitfalls. Particularly, we discuss designing interactivity into the e-learning process.